PERSAMAAN UMUM JUMLAH EDGE DAN TITIK PADA CYCLE EXTENSION CUBIC GRAPH - Hambali, Mohamad Ibnu; ., Wamiliana; ., Fitriani (MATEMATIKA, 2014)
In this research we will discuss about cycle extension of cubic graph. The cubic graphs used are the cucic graph with n(V(G)) ≤ 8 and k ≥ 3, ; k is the length of the cycle C and li is the number of vertices or points on that located between and . The construction process for determining the use six operations which are M1, M2, M3, M4, M5, dan M6. The result of M1 process on is a non Hamiltonian cycle while the results of M2, M3, M4, M5, and M6 are Hamiltonian cycles. We also show that the number of vertives on the is n(V()) = n (V(G)) + 2 k , and the number of edges on the is n(E() = n (E(G)) + 3 k.